The effectiveness of distance education in light of the spread of the Coronavirus, From the teachers’ point of view in the northeastern Badia schools - Ibrahim, Sanaa Abdal Kareem (Journal of Educational and Psychological Sciences, 2021)
This study aimed to reveal the effectiveness of distance education in light of the spread of the Corona virus From the teachers’ point of view in the northeastern Badia schools, and to achieve the objectives of the study, the descriptive analytical approach was adopted, and the study sample consisted of (150) teachers’ in the northeastern Badia schools; who taught during the spread of Coronavirus through the distance education system, and the necessary data were collected using a questionnaire whose reliability factor was (0.825) and was applied to the study sample. The results of the study revealed that the study sample’s evaluation of the effectiveness of distance education in light of the spread of the Coronavirus from their point of view was average, and their evaluation was of the field of continuity of distance education, the field of obstacles to the use of distance education, the field of interaction of faculty members with distance education, and the field of interaction of students in using Distance education is medium, and the researcher recommended holding training courses for students, teachers and administrators for programs and applications related to distance education, in addition to workshops to train them on distance education tools and strategies, and the need to combine face education and distance education in educational institutions in the future, and provide self- learning materials. For students who are not benefiting from the educational platforms due to the unavailability of the Internet or because of the power outage.